2003
DOI: 10.1021/ac0301346
|View full text |Cite
|
Sign up to set email alerts
|

Lead Isotope Ratio Determination for the Forensic Analysis of Military Small Arms Projectiles

Abstract: A study focusing on the ability to utilize isotopic analysis of Pb used in small arms projectiles from varying geographic origin was undertaken using the GV Instruments Isoprobe multicollector inductively coupled plasma mass spectrometer. With the exception of two classes of ammunition, these samples were able to be distinguished from one another. Also, following rigorous normalization and mass bias correction, these data were compared to data collected by geochemists in localities corresponding to projectile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Earlier work has described rather significant variation of the observed isotopic composition of bullets within a single box, but no attempts to give a realistic model of these variations has been provided. [20], [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier work has described rather significant variation of the observed isotopic composition of bullets within a single box, but no attempts to give a realistic model of these variations has been provided. [20], [19].…”
Section: Discussionmentioning
confidence: 99%
“…Further, NRC suggested that lead isotope compositions of bullet lead should be further investigated. Earlier work on lead isotope determination of bullet lead have not focused on either descriptive statistics nor evaluation of bullet lead evidence [17], [18], [19], [20].…”
Section: The Classification Problemmentioning
confidence: 99%
“…Thus, the measurements of lead isotope ratios attract much attention in environmental, biological, archaeological, and geological sciences. [1][2][3][4][5][6][7][8] Thermal ionization mass spectrometry (TIMS) has been the method most generally used to obtain precise isotope ratios. However, the TIMS measurements are quite time consuming and require an initial chemical separation step carried out under very strictly clean laboratory environment to avoid contamination.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, laser ablation coupled to multicollector inductively coupled plasma mass spectrometry (LA‐MC‐ICP‐MS) has been used to provide high accuracy S isotope ratio measurements to identify counterfeit pharmaceutical drugs 10. Pb isotopic analysis using MC‐ICP‐MS has been shown to aid geographical/manufacturer sourcing of small arms projectiles 11. The potential of LA coupled to a sector field ICP‐MS instrument as a routine, rapid and reliable, analytical methodology for fingerprinting sources of Pb in forensic investigations involving paint samples from different mining sources has also been reported 12…”
mentioning
confidence: 99%
“…10 Pb isotopic analysis using MC-ICP-MS has been shown to aid geographical/manufacturer sourcing of small arms projectiles. 11 The potential of LA coupled to a sector field ICP-MS instrument as a routine, rapid and reliable, analytical methodology for fingerprinting sources of Pb in forensic investigations involving paint samples from different mining sources has also been reported. 12 Coated cardboard paper is widely used as a packaging material for all kinds of products including pharmaceuticals.…”
mentioning
confidence: 99%